Optimal base-stock policy for the inventory system with periodic review, backorders and sequential lead times. Issue 1 (3rd July 2008) - Johansen, Soren Glud; Thorstenson, Anders
We extend well-known formulae for the optimal base stock of the inventory system with continuous review and constant lead time to the case with periodic review and stochastic, sequential lead times. Our extension uses the notion of the 'extended lead time'. The derived performance measures are exact for Poisson demands.